Implications of Economic Partnership Agreements on agriculture: the case of Kenya’s horticultural sub-sector - Njua, Agnes Njoki (My University, 2017)
As a result of the dependency created during the colonial period and later through preferential trade initiatives, Europe has been and continues to be Kenya’s major trading partner. The current trade relationship between Kenya and Europe was recently formalised after the signing of the Economic Partnership Agreements (EPAs), a reciprocal and comprehensive free trade agreement that is legal under Article XXIV of General Agreement on Tariff and Trade (GATT). The agreement has caused great debate on whether it is truly beneficial to Kenya in light of the asymmetrical levels of development, with many questioning what role the agreement will play towards sustainable growth and development and specifically in the horticultural sub-sector. Sharing the pitfalls of both the Lomé Convention and Cotonou Agreement that failed to deliver the expected development there is reason to believe that few gains will be made by signing the EPAs as they are today. The horticultural sub-sector is a major provider of employment, especially in the rural areas, and is the second largest foreign exchange earner for Kenya. Facing increasing domestic and international demand, coupled with continued and enhanced market access to Europe, participation in the highly profitable sub-sector has the potential of transforming rural agriculture by presenting an opportunity for small-scale farmers to increase their income and reduce poverty. As a non-Least Developed Country (LDC) country, the loss of trade preference for Kenya could severely undermine export competitiveness and damage the horticultural sub-sector which is heavily dependent on exports to the European Union (EU). The main objectives of the Kenyan government for signing the EPAs include sustaining the current market preferences, avoiding macroeconomic instability and the disruption of economic activities in the agricultural sector. The study found that, given Kenya’s substantial dependency on the horticultural sub-sector and the limited trade schemes options available to engage in trade with the EU, the government had no option but to sign the EPAs. The failure to diversify the economy, inadequate public institutions, insufficient human and financial capacity, declining public investments in agriculture and limited intra-African trade and the failure to seek other market destinations are some of the reasons why the government entered into the agreement. The Kenyan government needs to aggressively increase investments in the agricultural sector in order to enable transformation and promote diversification through value addition. Manufacturing should be prioritised as this will enable the economy to become less exposed to commodity price fluctuations. The government should seek to develop and increase intraAfrica trade as well as explore other market options in Asia, North America and South America in efforts to lessen Kenya’s dependency on Europe. Further, Kenya and other African Caribbean and Pacific (ACP) countries should, instead of signing a Free Trade Agreement (FTA) such as an EPA, collectively call for an improved EU General Scheme of Preference (GSP) tailored for both LDC and non-LDC countries that would provide real cooperation and development.
A Master’s degree Dissertation presented in partial Fulfilment for the Award of Master of Management in Public Policy at University of Witwatersrand, Wits School of Governance (WSG), 2016
Keywords: Kenya--Economic policy; Kenya--Foreign economic relations; Free trade--Kenya; Agriculture--Kenya